A decade analysis of flower area, production and instability index – A review - ANSHUL KUMAR; PATHANIA, SABHYA; KASHYAP, BHARATI; DHIMAN, SITA RAM; Y.C. GUPTA (Journal of Ornamental Horticulture, 2024)
The floriculture industry in India has witnessed significant transformations over the past decade. This sector, encompassing the cultivation of flowers and ornamental plants, is not only pivotal for domestic markets but also holds substantial export potential. This review paper presents a comprehensive analysis of the area and production of major flower crops across Indian states over a decade, from 2014-15 to 2023-24. Utilizing ten years of data, we investigate the growth dynamics and instability in the floriculture sector, focusing on key flower crops. The study employs the Della Valle Instability Index to quantify the volatility in production, providing a nuanced understanding of the sector’s stability. Additionally, the Compound Growth Rate (CGR) is calculated to evaluate the long-term growth trends of flower crops. Our findings reveal significant variations in the production of major flower crops across different states, highlighting both growth opportunities and challenges in the sector. The Della Valle Instability Index indicates varying levels of stability, with certain states exhibiting higher volatility due to factors such as climatic conditions, market fluctuations, and policy impacts. The CGR analysis underscores a positive growth trajectory for some crops, while others show stagnation or decline, necessitating targeted interventions. This review emphasises the importance of strategic planning and policy support to enhance the stability and growth of the floriculture industry in India. By identifying key trends and instability factors, this paper provides valuable insights for policymakers, researchers, and stakeholders in the agricultural sector. The findings aim to inform future research and development initiatives, fostering India’s more resilient and productive floriculture sector. In conclusion, this decade-long analysis highlights the critical need for a balanced approach to managing growth and stability in flower crop production, ensuring sustainable development in India’s floriculture industry.